2010
DOI: 10.1038/ncb2122
|View full text |Cite
|
Sign up to set email alerts
|

Competition amongst Eph receptors regulates contact inhibition of locomotion and invasiveness in prostate cancer cells

Abstract: Metastatic cancer cells typically fail to halt migration on contact with non-cancer cells. This invasiveness is in contrast to normal mesenchymal cells that retract on contact with another cell. Why cancer cells are defective in contact inhibition of locomotion is not understood. Here, we analyse the dynamics of prostate cancer cell lines co-cultured with fibroblasts, and demonstrate that a combinatorial code of Eph receptor activation dictates whether cell migration will be contact inhibited. The unimpeded mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
282
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(293 citation statements)
references
References 41 publications
10
282
1
Order By: Relevance
“…In metastatic prostate (PC-3) cells RhoA activation due to the engagement of ephrin-A ligands and EphrinA receptors activates RhoA leading to actomyosin contraction and lamella withdrawal, i.e. homotypic CIL [36]. Fibroblast ephrin-B ligands interact with PC-3 EphrinB receptors, triggering sustained activation of Cdc42 and filipodia extension, thereby stimulating PC-3 cell migration and leading to defective CIL [36].…”
Section: Discussionmentioning
confidence: 99%
“…In metastatic prostate (PC-3) cells RhoA activation due to the engagement of ephrin-A ligands and EphrinA receptors activates RhoA leading to actomyosin contraction and lamella withdrawal, i.e. homotypic CIL [36]. Fibroblast ephrin-B ligands interact with PC-3 EphrinB receptors, triggering sustained activation of Cdc42 and filipodia extension, thereby stimulating PC-3 cell migration and leading to defective CIL [36].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cancer cells may circumvent the tumour-suppressive effect of Eph signalling by downregulating the expression of ephrin ligands, as an alternative to either losing Eph receptor expression or acquiring Eph receptor-inactivating mutations 35,36 . Further adding to the complexity of Eph receptor function in cancer cells, ephrin-B2-dependent EphB3/EphB4-Cdc42 signalling has been shown to enhance migration and cause defective contact inhibition of locomotion in prostate cancer 37 . Therefore, the tumour-promoting or tumour-suppressing effects of the Eph receptors appear to be determined on the cellular context.…”
Section: Discussionmentioning
confidence: 99%
“…Héroult et al (2006) tested the effects of EphB4 over-expression on the migration of A375 melanoma cells, and concluded that EphB4 alone confers an enhanced migratory phenotype independent of ephrin-B2-induced forward signalling [20,22]. Other significant findings in this study…”
supporting
confidence: 64%
“…These results were also demonstrated in murine mammary and ovarian xenograft models [15], and compared to models that over-expressed EphB4 which showed accelerated tumour progression and increased lung metastasis [145]. In the second key study with direct relevance to this study, Héroult et al (2006) showed that EphB4 promotes site-specific metastatic TC dissemination through interaction with EC expressed ephrin-B2 [22].…”
mentioning
confidence: 81%
See 1 more Smart Citation